Neoarchean-Paleoproterozoic granulite-facies metamorphism in Uzkaya Salma eclogite-bearing melange, Belomorian Province (Russia) - Li, Xiaoli; Zhang, Lifei; Wei, Chunjing; Slabunov, Alexander I.; Bader, Thomas (Precambrian Research, 2017)
A TTG gneiss of Uzkaya Salma, Belomorian Province and retrogressed eclogites embedded in it have been thoroughly analyzed. The gneiss is made of plagioclase, K-feldspar, biotite, and quartz with accessory epidote, chlorite, titanite and zircon. The retrogressed eclogite is featured by garnet, clinopyroxene, plagioclase, amphibole, and quartz with subordinate orthopyroxene, muscovite, epidote, and melt phase exhibiting a typical symplectic texture. Diversity of compositional zonation in garnets depends on different garnet diameters and is related to ion diffusion between garnet and clinopyroxeneiamphibole during retrogression. Clinopyroxene is mostly diopside, although a few Jd-enriched varieties (Na-rich clinopyroxene) have been found at some sites, indicating an omphacite precursor. Plagioclase formed in both symplectites and aggregates displays a wide compositional range, revealing alteration at certain PT conditions. K-bearing ternary feldspar casually occurs in association with muscovite, zoisite/epidote, and melt phase, denoting a partial melting product. Phase equilibria modeling, combined with mineralogical constrains yielded a clock-wise PT path with peak conditions of P >= 17-18 kbar, T = 700-750 degrees C, followed by granulite-facies at P = 13-15 kbar, T = 800-850 degrees C, and, eventually into the (upper) amphibolite-facies of T <= 700-750 degrees C at lower pressures. A geothermal gradient of similar to 12-13 degrees C/km is inferred accordingly, rather common for the Belomorian eclogites and some other eclogite/high-pressure granulite belts (EHPG) on Earth. Zircon U-Pb dating shows that the TUG gneiss formed at 2.73-2.74 Ga, while the protolith of the eclogites may have experienced magmatism/anatexis at >= 2.77 Ga. There is no implication of any Archean eclogite-facies metamorphism in this work. Nevertheless, a granulite-facies metamorphism, featured by a diopside + plagioclase + amphibole garnet, orthopyroxene assemblage, has been determined at 2.7 Ga that also superimposed the host gneiss. Afterwards, due to regional plume activities, repeated thermal events of granulite-facies metamorphism, occurred at least locally at 2.4-2.5 Ga. An eclogite-facies metamorphism at 1.9-2.0 Ga was dated only that corresponds to the Lapland-Kola orogeny. Further retrogression into the (upper) amphibolite-facies was documented at 1.8 Ga. The proposed metamorphic PT path corresponds to the late Paleoproterozoic eclogite-facies event, while before that, only (repeated) granulite-facies metamorphism has been recorded by zircons. (C) 2017 Elsevier B.V. All rights reserved. National Nature Science Foundation of China [41202032, 412111062, 41311120071] SCI(E) ARTICLE 257-283 294